Protective role of gluteofemoral obesity in erosive oesophagitis and Barrett's oesophagus. Issue 2 (5th March 2013) - Rubenstein, Joel H; Morgenstern, Hal; Chey, William D; Murray, Joseph; Scheiman, James M; Schoenfeld, Philip; Appelman, Henry D; McMahon, Laurence; Metko, Val; Kellenberg, Joan; Kalish, Tal; Baker, Jason; et al.
Abstract : Objective: Abdominal obesity has been associated with erosive oesophagitis (EO) and Barrett's oesophagus (BO). As gluteofemoral obesity protects against diabetes mellitus and cardiovascular disease, we hypothesised that gluteofemoral obesity would be inversely associated with EO and BO. Design: We conducted a cross-sectional study on 822 male colorectal cancer screenees who were recruited to also undergo upper endoscopy. An additional 80 patients with BO clinically detected by upper endoscopy referred for clinical indications were recruited shortly after their diagnoses of BO. Logistic regression was used to estimate the effects of abdominal obesity (waist circumference), gluteofemoral obesity (hip circumference) and waist-to-hip ratio (WHR) on EO and BO (vs neither condition). Results: There were 225 cases of either BO or EO and 675 controls. After adjustment for potential confounders, a positive association was observed between waist circumference and BO and/or EO, which became stronger with further adjustment for hip circumference. In contrast, hip circumference was inversely associated with BO and/or EO. Compared with the lowest quartile of WHR, the adjusted ORs were 1.32 (95% CI 0.747 to 2.33) for the 2nd quartile, 1.54 (95% CI 0.898 to 2.63) for the 3rd quartile, and 2.68 (95% CI 1.57 to 4.55) for the highest quartile. Similar results were obtained for BO and EO treated as separate outcomes. Conclusions: In a population of older, mostly overweight men, the distribution of obesity is associated with the presence of EO and BO. Abdominal obesity appears to increase the risk of these outcomes, whereas gluteofemoral obesity may be protective.